Protective effects of Artemisia herba-alba in diabetic peripheral artery disease mediated via inhibition of advanced glycation end products - Li Sun; Fang Liu; Jianting Li; Pei Sun (Kuwait Journal of Science)
Artemisa herba-alba is an important medicinal herb with immense pharmacological potential. The present study evaluated the effects of Artemisia herba-alba extract (AHE) on peripheral artery disease in diabetic rats via inhibition of advanced glycation end products (AGEs). The in vitro AGE inhibiting potential of AHE was determined by spectrofluorimetric method. The blood glucose levels and HbA1c (A1C) of the rats from each group were determined by automatic analyser. The levels of AGEs in vascular smooth muscle cells (VSMCs) of different rat groups were determined by western blotting. Expression of COX-1 and COX-2 were determined by qRT-PCR. Results showed that AHE inhibited the AGEs formation in vitro and exhibited an IC50 of 45 µg/mL which was significantly lower than that of standard AGEs inhibitor aminoguanidine (IC50: 60 µg/mL).  Analysis of metabolic profiles revealed that AHE normalised the blood glucose, cholesterol, and triglycerides with no apparent changes on Hb1Ac levels. Western blot analysis showed that AHE exhibited protective effects in VSMCs of diabetic rats by inhibiting the production of AGEs. Moreover, the expression of COX-2 was inhibited by AHE in diabetic rats. However, the expression of COX-1 remained unaltered. Collectively, the results revealed AHE inhibits AGEs formation in vitro and in VSMCs of diabetic rats. These findings point towards the potential of AHE in the management of diabetic peripheral artery disease.